Models of legal regulation of organ or tissue removal from dead persons - Гринчак, Сергій Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article examines the models of legal regulation of organ or tissue removal from a donor-cadaver whichused in the world of transplantation; their classification are proposed, the advantages and disadvantages ofthese models are identified.